Variation of body temperature after sponge bath in stable very low birth weight preterm neonates - Mangalgi, Sharanabasavesh; Upadhya, Namratha (Indian Journal of Child Health, 2022)
Aim: To observe the variation of the body temperature after routine sponge bath in stable very low birth weight preterm babies. Methods: 74 babies admitted to the neonatal intensive care unit (NICU) of a tertiary care teaching hospital were enrolled. The inclusion criteria were babies with corrected gestational age between 28 and 36 weeks, birth weight